Maternal Metabolic Status and Orofacial Cleft Risk: A Case-Control Study in Thailand - Araya Pisek; Christy M. McKinney; Benja Muktabhant; Waranuch Pitiphat (Elsevier, 2024)
ABSTRACT: Objectives: Metabolic syndrome (MetS) has been suggested to play a role in congenital defects. This study investigated the association of MetS and its components with orofacial clefts (OFCs). Methods: We conducted a case-control study in Northeast Thailand. Ninety-four cases with cleft lip, with or without cleft palate, were frequency matched with 94 controls on the infant's age and mother's education. We administered a mother's health questionnaire and collected anthropometric measurements and blood samples. Multiple logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Subgroup analyses were performed among infants without a family history of OFCs, mothers who were not currently breastfeeding, and mothers who were >6 months postpartum. Results: When compared to mothers of normal weight, the OR associated with OFCs were 2.44 (95% CI, 1.04-5.76, P = .04) in overweight mothers, and 3.30 (95% CI, 1.14-9.57, P = .03) in obese mothers. Low HDL-C raised the risk of OFCs 2.95 times (95% CI, 1.41-6.14, P = .004) compared to normal HDL-C levels. Mothers with 4 or 5 features of MetS were 2.77 times as likely to have the affected child than those who did not (95% CI, 0.43-17.76), but this difference was not statistically significant (P = .28). Subgroup analyses showed similar results, uncovering an additional significant association between underweight mothers and OFCs. Conclusions: The results indicate a robust association between underweight and overweight/obese maternal body mass index and increased OFC risk. Additionally, low HDL-C in mothers is linked to an elevated risk of OFCs. Further research is needed to evaluate if promoting strategies to maintain optimal body weight and enhance HDL-C levels in reproductive-age and pregnant women icould contribute to a reduction of the risk of OFCs in their progeny.